Achieving equity for International Medical Graduates: a systematic review - Sangeeta G. Saxena; Elizabeth Tisdell; Elana Farace; Thomas Godfrey; Betsy Aumiller; Esther Dell; Omrana P. Razzak; Bernadette N. Kumar; Kristin K. Sznajder (Frontiers in Medicine)
IntroductionForeign-born and foreign trained International Medical Graduates (FIMGs) face greater challenges in acculturation to their host countries than IMGs who train abroad and return to practice in their home country. As FIMGs are likely to fulfill a shortage of physicians in High Income Countries in the foreseeable future, we conducted a systematic review of literature to identify acculturation interventions that help FIMGs assimilate better in their host country health systems. This improves their productivity and satisfaction, allows health systems to be more accepting of FIMGs, and most importantly, enhances patient outcomes.MethodsFollowing the PRISMA statement, we searched PubMed, Embase, PsycINFO, CINAHL, Web of Science for all peer-reviewed articles using keywords “international medical graduate”, “overseas trained doctor”, “overseas trained physician”, “foreign trained doctor”, “foreign trained physician” (group A); and “discrimination” and “microaggressions” (group B) published between January 1st, 2000 to October 24th, 2021.ResultsThe 46 studies included in this review fall into three groups – acculturation interventions for FIMGs, FIMG’s perceptions of what they found useful, and trainers’ perspectives on ‘what works’. This review also includes interventions that pivoted to the online mode during the Covid-19 pandemic, making the findings relevant, as this is likely to the norm in the future. Acculturation requires training on clinical protocols, host country and health system culture and norms and communication, language and self-awareness skills.DiscussionMuch work remains to be done. Interventions need to be tailored to suit the unique needs of FIMGs from 150+ countries, trainings require a foundation of theoretical frameworks, additional professional, personal and social support to be provided, life course related changing needs demand attention and the preparedness of host country health systems to accept FIMGs require enhancement.